Privacy, Confidentiality, and Data Protection: Ethical Considerations in the Use of the Internet - Tri Indriasari, Devi; Karman, Karman (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The Internet has had a profound, impact on society, enabling numerous benefits while also presenting significant challenges. While it has revolutionized communication, information access, and business operations, it has also created new ethical challenges, particularly with regards to inappropriate or negative content. Cybercrime, misinformation, disinformation, and user data exploitation are just a few examples of these issues. As the Internet's reach and influence continue to expand, it is critical to recognize and adhere to ethical principles in the digital world. This article aims to explore the importance of ethical principles in Internet use and their role in mitigating negative impacts. To achieve this objective, the paper conducts a literature review towards policy document and analyzes bibliometrics data against scholarly article databases indexed by Scopus and identify key point regarding ethical discourse. The article delves into the ethical implications of the Internet, including privacy concerns, confidentiality, decision-making, and data protection. In conclusion, it posits that the Internet should not be viewed simply as a tool but as a cultural artifact with the potential to shape society for better or worse. Therefore, it is our responsibility as users and stakeholders to understand and uphold ethical standards to ensure the responsible and equitable use of this powerful technology.